Achieving Work and Love Authorship in Emerging Adulthood: Types, Psychosocial Correlations, and Precursors. (August 2016) - Shulman, Shmuel; Hakhmigari, Maor Kalfon; Michaeli, Yossi; Tuval-Mashiach, Rivka; Dickson, Daniel J.
The present study examined the achievement of work and romantic authorship in 100 Israeli emerging adults (54 men) who were followed from age 22 to 29. At the age of 29, participants were asked to talk about their current occupational and romantic statuses and the changes they underwent and to reflect on the meaning of these changes. Qualitative analyses of the interviews yielded four types of achieving work and romantic authorship: in both or either domain and in only work or only romantic authorship. These types were associated with different changes in goal pursuit and well-being over time and differed across gender. Analysis of our longitudinal data also showed that low self-efficacy combined with low maternal support measured 7 years earlier was associated with the lack of authorship in all domains. Yet, when low efficacy was combined with elevated paternal support, it predicted the achievement of work authorship.